Design and development of coconut palm collector - Muhammad Azam, Ismail (2011)
This project concerns on the assessment of making a product, the coconut palm collector which will consider all aspects and concepts for satisfaction of the users. The main objectives of this project are to design and develop the coconut palm collector. The project was start with development of design concepts that combine several ideas. The design concept generated then was analyzed using the matrix chart. All parameters and factor that related to customer satisfaction such as easy to maintenance or easy to uses was analyzed. The design concept that gave highest marks during analysis stage was selected as a final design. The structural three-dimensional solid modeling for final design concept that has been selected was developed using the computer-aided drawing software namely Solidwork. All the factors that need to consider was taken during material selection for fabrication stage. The factor was considered for material selection such as lightweight, not rust, hardness, cheap, and others are taken for fabrication process. After fabrication process, the final product has been tested to ensure that the product is functional or not. If the product is not following specification, some modification will be made. The modification process will be repeating until the products achieve the desire specification.